2002
DOI: 10.1292/jvms.64.91
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Foot-and-Mouth Disease Virus from Japanese Black Cattle in Miyazaki Prefecture, Japan, 2000.

Abstract: ABSTRACT. Four outbreaks of foot-and-mouth disease (FMD) occurred from March to May 2000 in Miyazaki and Hokkaido Prefectures, Japan. FMD virus isolation was achieved by sampling probang materials from Japanese Black cattle in the third case found in Miyazaki Prefecture. The probang materials were inoculated to bovine kidney (BK) and bovine thyroid cell cultures. CPE was observed in the BK at two days post-inoculation. Specific amplified DNA segments for FMD virus (FMDV) were detected by reverse transcriptase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 0 publications
0
43
0
1
Order By: Relevance
“…Therefore, at first, to deny FMD virus (FMDV), reverse transcriptase-PCR, antigen detection enzyme-linked immunosorbent assay (ELISA), and antibody detection ELISA for FMDV were carried out using mixed scabs from 7 sheep and each serum from 10 sheep as described previously 16 .…”
Section: Examination For Foot-and-mouth Disease Virusmentioning
confidence: 99%
“…Therefore, at first, to deny FMD virus (FMDV), reverse transcriptase-PCR, antigen detection enzyme-linked immunosorbent assay (ELISA), and antibody detection ELISA for FMDV were carried out using mixed scabs from 7 sheep and each serum from 10 sheep as described previously 16 .…”
Section: Examination For Foot-and-mouth Disease Virusmentioning
confidence: 99%
“…The other disadvantage of IS-ELISA is that the manual recommends sampling vesicular fluid or tissue and culture fluid, but such samples may not be available in preclinical and/or subclinical diagnoses. For instance, the cattle in the 2000 FMD outbreak in Japan did not show clear vesicles (6,8,16). These problems would be solved if plasma and/or saliva could be used as the sample.…”
Section: And Nucleic Acid Recognition Methods Such As Reverse Transcmentioning
confidence: 99%
“…12 Pearson chi-square test and Student's t-test were used for analyzing the statistical significance of the differences in virus isolation rates between the ZZ-R 127 and the IB-RS-2 cells and in virus titers in the ZZ-R 127 and the IB-RS-2 cells, respectively. Table 1 In total, 292 and 144 samples were collected from the experimentally infected goats and pigs, respectively.…”
Section: Research-article2013mentioning
confidence: 99%
“…At the National Institute of Animal Health, Japan (NIAH), primary bovine kidney cells and IB-RS-2 cells are routinely used for diagnostic tests for FMD. 6,12 A previous study 2 reported that the fetal goat tongue cell line ZZ-R 127 was highly sensitive for the isolation of FMDV. The study evaluated its availability for FMDV isolation using cell culture supernatants and epithelial suspensions of various FMDV strains.…”
mentioning
confidence: 99%